A case of angioimmunoblastic T-cell lymphoma coexisting with castleman disease - Zhan, Lianshan; Wang, Long; Wu, Hongyan; Chen, Zhongjiao; Wang, Lina (Human Pathology Reports, 2025)
Angioimmunoblastic T-cell lymphoma (AITL) is a rare, mature T-cell lymphoma with diagnostic challenges. Its coexistence with Castleman disease (CD) is exceptionally uncommon and complicates diagnosis and management. We report a 67-year-old male with bilateral cervical lymphadenopathy. Imaging showed enlarged lymph nodes with prominent vascularity and a “rim sign.” Initial pathology suggested CD, with preserved lymph node architecture, atrophic germinal centers, and “lollipop” structures. Further evaluation, however, revealed diffuse proliferation of atypical T-cells. Immunohistochemistry showed atypical cells expressing follicular helper T-cell markers (CD10, PD1, BCL6). Molecular analysis confirmed monoclonal TCRγ gene rearrangement, and flow cytometry identified an abnormal CD4 + CD7 − T-cell clone. These findings established the diagnosis of AITL coexisting with CD. This case highlights the high diagnostic hurdles of coexisting AITL and CD, emphasizing the critical need for comprehensive morphological, immunophenotypic, and molecular analyses for accurate diagnosis and optimal patient management.